THE PRINCIPLE OF FORMING LEXICOGRAPHIC COMPETENCE IN PRIMARY CLASS STUDENTS AND TECHNOLOGIES (Academicia Globe: Inderscience Research, 2023)
In this article, you can get enough information about the principles and technologies of the modern approach to the formation of lexicographic competence in elementary school students.